Method for constructing super-hydrophobic surface based on amphiphilic hollow silicon dioxide Janus nanoparticles
Through the preparation technology of amphiphilic hollow silica Janus nanoparticles, the high preparation cost and complex process of the superhydrophobic coating construction on the enamel surface are solved, and a fast and efficient superhydrophobic surface is achieved, with antibacterial and anti-protein adhesiveness. Attach the effect and maintain the hydrophobic properties for a long time.
Patent Information
- Application Number
- CN202411430156.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-03
AI Technical Summary
The existing superhydrophobic surface preparation methods have problems such as high preparation cost, complex process and long construction time in the application of enamel surfaces, making it difficult to achieve a fast, efficient and safe superhydrophobic coating.
Spherical nanoparticles were prepared by hydrolysis-condensation reaction, combined with paraffin and surfactant for emulsification, followed by modification using γ-aminopropyltriethoxysilane and polypeptide, and finally 1H was added, 1H,2H-perfluorooctyltriethoxysilane, through ultrasonic and stirring, the superhydrophobic properties of the surface are achieved.
It has achieved rapid and efficient construction of superhydrophobic coating, antibacterial and anti-protein adhesion effects on the surface, and the water droplet contact angle reaches 160°, and the superhydrophobic performance remains maintained after artificial saliva co-culture.
Smart Images

Figure CN119242081A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrophobic surface materials, and in particular to a method for constructing a super hydrophobic surface based on amphiphilic hollow silica Janus nanoparticles. Background Art
[0002] Superhydrophobic materials have shown broad application prospects in the biomedical field due to their unique surface properties. This material can significantly reduce the contact area between the surface and the liquid, thereby reducing the risk of bacterial attachment and biological contamination, and thus plays an important role in medical equipment and biological applications. At present, the main preparation methods of superhydrophobic surfaces include etching, deposition, anodization, template method, etc., but due to the harsh reaction conditions, high preparation costs, and complex processes of the above methods, the construction of superhydrophobic layers on the enamel surface is limited. Therefore, finding a fast, efficient, and safe method for constructing superhydrophobic enamel coatings is currently a hot topic of research.
[0003] Janus particles have outstanding characteristics such as structural asymmetry, multifunctionality, customizability, biocompatibility and safety. In addition, as scholars have discovered the key adhesion polypeptide sequence in the salivary acquired membrane (SAP), it is of great significance to use the polypeptide adhesion sequence as the adhesion end of the amphiphilic particles and link the hydrophobic long carbon chain at the other end to construct an efficient and fast amphiphilic superhydrophobic coating.
[0004] At present, Jiansu Li et al. (Xiao Yang, Fuhui Huang, Xinyuan Xu, Yanpeng Liu, Chunmei Ding, Kefeng Wang, Anran Guo, Wei Li, and Jianshu Li. Bioinspired from Salivary Acquired Pellicle: A Multifunctional Coating for Biominerals. Chemistry of Materials. 2017, 6, 09) soaked the polypeptide sequence DDDEEKCPAMAM adhered to the surface in different concentrations of heptafluorodecanoyl chloride and an equal amount of triethylamine ether solution for 4 hours to obtain a superhydrophobic surface. However, the hydrophobic coating constructed by this method takes a long time and is inconvenient to use. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for constructing a super-hydrophobic surface based on amphiphilic hollow silica Janus nanoparticles to solve the above problems.
[0006] The technical solution of the present invention is achieved as follows: a method for constructing a super-hydrophobic surface based on amphiphilic hollow silica Janus nanoparticles, comprising the following preparation steps: Step 1: preparing monodisperse spherical silica particles through a hydrolysis-condensation reaction; Step 2: Add nano-silica to deionized water, add solid paraffin and surfactant after ultrasonication, heat to 70-90°C and emulsify at high speed for 2 minutes to obtain Pickering emulsion, cool and wash to obtain silica nanoparticles half-covered by paraffin; Step 3, dispersing the silica nanoparticles prepared in step 2 in an ethanol aqueous solution, stirring evenly, adding γ-aminopropyltriethoxysilane, then adjusting the pH, and then stirring at room temperature for 12 hours to obtain γ-aminopropyltriethoxysilane-modified silica nanoparticles; Step 4: After the number of amino groups of the nano-silica obtained in step 3 is quantified by acid orange II, DDDEEKC-PEG100-2000-COOH - After mixing with 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride for 30 minutes, the mixture was added to the ultrasonically dispersed γ-aminopropyltriethoxysilane-modified nano-silica solution, followed by the addition of hydroxysuccinimide. The above reactions were all carried out in a 4% ethanol / water solution. The solution was then stirred at 4°C for 20 hours, centrifuged and freeze-dried to obtain polypeptide-modified nano-silica. Step 5, adding the nano-silica obtained in step 4 to an ethylene glycol aqueous solution, adding 1H,1H,2H,2H-perfluorooctyltriethoxysilane, and stirring for 20 hours to obtain nano-silica particles modified with 1H,1H,2H,2H-perfluorooctyltriethoxysilane; Step 6: Dissolve the nano-silica obtained in step 5 in ultrapure water at 6-10 mg / ml, disperse it evenly with a cell disruptor, take 200 ml and add it to the well plate with the enamel slice, let it stand for 10 minutes, rinse the enamel slice three times with ultrapure water, and dry it to obtain a superhydrophobic enamel surface.
[0007] Furthermore, in step 1, the particle size of the nano-silicon dioxide is 20-500 nm.
[0008] Furthermore, in step 2, the mass fraction of water is 80%-90%, the mass fraction of nano-silicon dioxide is 1‱-2‱, the mass fraction of paraffin is 10%-20%, and the surfactant is 5nmol~10nmol.
[0009] Furthermore, in step 2, the emulsification speed is 5000-18000 rpm.
[0010] Furthermore, in step 2, the emulsification temperature is 70-90°C.
[0011] Furthermore, in step three, the ethanol aqueous solution is a mixed solution of anhydrous ethanol and water, the volume ratio is 90-50ml:10-50ml, the mass fraction of γ-aminopropyltriethoxysilane is 4%-20%, and the pH is adjusted to 3-4.
[0012] Further, in step 4, NH4 + With COOH - The molar ratio of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride to COOH is 3-5:1. - The molar ratio of ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride to N-hydroxysuccinimide is 6-10:1, the molar ratio of ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride to N-hydroxysuccinimide is 1:1, and the molecular weight distribution range of polyethylene glycol is PEG100-2000.
[0013] Furthermore, in step five, the volume ratio of ethylene glycol to water in the ethylene glycol aqueous solution is 3-7:7-3, and the mass fraction of 1H,1H,2H,2H-perfluorooctyltriethoxysilane is 4%-20%.
[0014] The beneficial effects of the present invention are: By using the acquired membrane adhesion polypeptide sequence as the bonding end and 1H,1H,2H,2H-perfluorooctyltriethoxysilane as the hydrophobic end, amphiphilic Janus particles were constructed, and a fast and efficient surface super-hydrophobic coating was successfully constructed, giving the surface antibacterial and anti-protein adhesion effects; Using the adhesion polypeptide sequence of the acquired membrane as the bonding end and 1H,1H,2H,2H-perfluorooctyltriethoxysilane as the hydrophobic end, amphiphilic Janus particles were constructed with regular morphology and controllable structure. The amphiphilicity of SiO2Janus particles is used to orient them on the surface, with the hydrophilic hemisphere facing the surface and the hydrophobic hemisphere facing the air side, thus achieving super-hydrophobicity on the surface. At the same time, the specific amino acid sequence on the polypeptide sequence specifically adsorbs with the hydroxyapatite on the surface, fixing the SiO2Janus particles on the surface, so that the coating is formed efficiently and quickly; The contact angle between the super-hydrophobic coating prepared by the present invention and water is as high as 160°, and the contact angle of water dropped onto the coating surface 30 minutes later is still greater than 150°. When the coating is co-cultured with artificial saliva for 3 days, the surface still has a super-hydrophobic effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0016] Figure 1 Specific embodiments of the present invention (a) is the contact angle of water dropped onto the enamel surface at 0 min, (b) is the contact angle of water dropped onto the enamel surface at 30 min, and (c) is the contact angle of the enamel surface after being co-cultured with artificial saliva for three days; Figure 2 A contact angle test diagram further illustrating the hydrophobic performance of the coating surface in accordance with a specific embodiment of the present invention; Figure 3 This is a graph showing the particle size variation of the particles synthesized according to a specific embodiment of the present invention (a represents nano-silica, b represents nano-silica modified with γ-aminopropyltriethoxysilane, c represents nano-silica modified with polypeptide, and d represents nano-silica modified with 1H,1H,2H,2H-perfluorooctyltriethoxysilane); Figure 4 EDS is a specific embodiment of the present invention Figure 1 ; Figure 5 EDS is a specific embodiment of the present invention Figure 2 ; Figure 6 This is the FT-IR image of the hydrophobic coating on the enamel surface according to the specific embodiment of the present invention; Figure 7 (a) is an electron microscope image of enamel according to a specific embodiment of the present invention, and (b) is an electron microscope image of coating. DETAILED DESCRIPTION
[0017] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] In the description of the present application, it should be noted that the terms used herein are only for describing specific embodiments, and are not intended to limit the exemplary embodiments according to the present application. For ease of description, the sizes of the various parts shown in the drawings are not drawn according to the actual proportional relationship. The technology, methods and equipment known to ordinary technicians in the relevant field may not be discussed in detail, but in appropriate cases, the technology, methods and equipment should be regarded as part of the authorization specification. In all examples shown and discussed here, any specific value should be interpreted as merely exemplary, rather than as a limitation. Therefore, other examples of the exemplary embodiments may have different values. It should be noted that similar numbers and letters represent similar items in the following drawings, so once an item is defined in one drawing, it does not need to be further discussed in subsequent drawings.
[0019] Embodiment 1: A method for constructing a super-hydrophobic coating based on amphiphilic silica Janus particles comprises the following steps: (1) Preparation of Nano-Silica Add 1%-6% deionized water to 200-250mg ethanol solution, then add 5-20ml tetraethyl orthosilicate TEOS, stir well to make it evenly dispersed, then add 5-20ml ammonia water, and make it fully react at 4°C for 8-12 hours to obtain 20-500nm silicon dioxide; (2) Preparation of amphiphilic nano-silica Janus particles Add 1‱-2‱ mass fraction of nano-silica and 80%-90% mass fraction of deionized water into a beaker, ultrasonically disperse for 30 minutes, then add 10%-20% mass fraction of paraffin and 5nmol~10nmol of surfactant-didecyldimethylammonium bromide, heat to 70-90℃, and emulsify with high-speed stirring at 5000-18000 rpm for 2 minutes to obtain silica nanoparticles with half of the sphere covered by paraffin.
[0020] The silica nanoparticles covered with paraffin are dispersed in an ethanol aqueous solution, ultrasonicated at 300W for 20-60 minutes, 4%-20% by mass of γ-aminopropyltriethoxysilane is added, and then transferred to a three-necked flask, the pH is adjusted to 3-4 with acetic acid, stirred at room temperature for 12-24 hours, and then the nano-silica is separated from the paraffin by high-speed centrifugation, and then washed and centrifuged three times alternately with cyclohexane and anhydrous ethanol to remove acetic acid and excess paraffin, and dried to obtain γ-aminopropyltriethoxysilane-modified nano-silica particles.
[0021] Finally, the nano-silicon dioxide particles are prepared by calcining in a muffle furnace at 500° C. for 3-6 hours.
[0022] The ethanol aqueous solution (mixture of anhydrous ethanol and water) is prepared by mixing anhydrous ethanol and deionized water in a volume ratio of (90-50) ml: (10-50) ml.
[0023] After the γ-aminopropyltriethoxysilane modified nano-silica particles were quantitatively measured with acid orange for the number of amino groups, 10-25 mg of DDDEEKC-PEG100-2000-COOH- and 5-20 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride were mixed. At the same time, 20 mg of γ-aminopropyltriethoxysilane modified nano-silica was ultrasonically dispersed in the solution. After 30 minutes, the two were mixed together, and then 5-15 mg of hydroxysuccinimide was added. The above reactions were all carried out in a 4% ethanol / water solution, and then the solution was stirred at 4°C for 20 hours, centrifuged, and freeze-dried to obtain peptide-modified nano-silica; In the above steps, NH4 + With COOH - The molar ratio of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride to COOH is 3-5:1. - The molar ratio of ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride to N-hydroxysuccinimide is 6-10:1, the molar ratio of ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride to N-hydroxysuccinimide is 1:1, and the molecular weight distribution range of polyethylene glycol is PEG100-2000.
[0024] Then, 20-40 mg of the peptide-modified nano-silica is dispersed in 1-5 ml of ethylene glycol aqueous solution, stirred evenly, and then 4%-20% of 1H,1H,2H,2H-perfluorooctyltriethoxysilane is added, and stirred at 4° C. for 20 hours to obtain 1H,1H,2H,2H-perfluorooctyltriethoxysilane-modified nano-silica; In the above steps, the volume ratio of ethylene glycol to water in the ethylene glycol aqueous solution is 3-7:7-3, and the mass fraction of 1H,1H,2H,2H-perfluorooctyltriethoxysilane is 4%-20%.
[0025] Construction of superhydrophobic surface The final nano-silica was dissolved in ultrapure water at 6-10 mg / ml, dispersed evenly with a cell disruptor, and 200 ml was added to the well plate with the enamel slice, left to stand for 10 minutes, the enamel slice was rinsed three times with ultrapure water, and dried to obtain a superhydrophobic enamel surface.
[0026] Embodiment 2 (1) Preparation of Nano-Silica Add 6% deionized water to 220ml of ethanol solution, then add 18ml of tetraethyl orthosilicate TEOS, stir well to make it evenly dispersed, then add 20ml of ammonia water, and let it react fully at 4°C for 8-12 hours to obtain 360nm silica.
[0027] (2) Preparation of amphiphilic nano-silica Janus particles Add 2‱ mass fraction of nano-silica and deionized water into a beaker, ultrasonically disperse for 30 minutes, then add 20% mass fraction of paraffin and 5nmol~10nmol of surfactant-didecyldimethylammonium bromide, heat to 90 degrees, and stir at 13000 rpm for 2 minutes to obtain silica nanoparticles with half of the sphere covered by paraffin.
[0028] The silica nanoparticles covered by paraffin were dispersed in an ethanol aqueous solution, ultrasonicated at 300W for 50 minutes, γ-aminopropyltriethoxysilane with a mass fraction of 20% was added, and the mixture was transferred to a three-necked flask, pH 4 was adjusted with acetic acid, stirred at room temperature for 24 hours, and the nano-silica was separated from the paraffin by high-speed centrifugation. The mixture was washed and centrifuged three times alternately with cyclohexane and anhydrous ethanol to remove acetic acid and paraffin, and the nano-silica particles modified with γ-aminopropyltriethoxysilane were obtained after drying. Finally, the nano-silica particles were prepared by calcining in a muffle furnace at 500°C for 3-6 hours.
[0029] The ethanol aqueous solution (a mixture of anhydrous ethanol and water) is a mixture of anhydrous ethanol and deionized water in a volume ratio of 9:1.
[0030] After the γ-aminopropyltriethoxysilane modified nano-silica particles were quantitatively measured with acid orange, 25 mg of DDDEEKC-PEG2000-COOH- and 20 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride were mixed. At the same time, 20 mg of γ-aminopropyltriethoxysilane modified nano-silica was ultrasonically dispersed in the solution, and then 15 mg of hydroxysuccinimide was added. The above reactions were all carried out in a 4% ethanol / water solution. Stir at 4°C for 20 hours, centrifuge, and freeze-dry.
[0031] 40 mg of peptide-modified nano-silica was dispersed in 15 ml of ethylene glycol aqueous solution, stirred evenly, and then 20% 1H,1H,2H,2H-perfluorooctyltriethoxysilane was added and stirred at 4°C for 20 hours to obtain 1H,1H,2H,2H-perfluorooctyltriethoxysilane-modified nano-silica.
[0032] (3) Construction of superhydrophobic surface The final nano-silica was dissolved in ultrapure water at 10 mg / ml, dispersed evenly with a cell disruptor, and 200 ml was added to the well plate with the enamel slice, left to stand for 10 minutes, the enamel slice was rinsed three times with ultrapure water, and dried to obtain a superhydrophobic enamel surface.
[0033] Embodiment 3 (1) Preparation of Nano-Silica Add 2% deionized water to 220 ml of ethanol solution, then add 8 ml of tetraethyl orthosilicate TEOS, stir well to make it evenly dispersed, then add 7 ml of ammonia water, and let it react fully at 4°C for 8-12 hours to obtain 100 nm silica.
[0034] (2) Preparation of amphiphilic nano-silica Janus particles Add 1‱ mass fraction of nano-silica and deionized water into a beaker, ultrasonically disperse for 30 minutes, then add 12% mass fraction of paraffin and 5nmol~10nmol of surfactant-didecyldimethylammonium bromide, heat to 80 degrees Celsius, and stir at 10,000 rpm for 2 minutes to obtain silica nanoparticles with half of the sphere covered by paraffin.
[0035] The silica nanoparticles covered by paraffin were dispersed in an ethanol aqueous solution, ultrasonicated at 300W for 30 minutes, 8% of γ-aminopropyltriethoxysilane was added, transferred to a three-necked flask, pH adjusted to 3.5 with acetic acid, stirred at room temperature for 12 hours, centrifuged at high speed to separate the nano-silica from the paraffin, washed and centrifuged three times alternately with cyclohexane and anhydrous ethanol to remove acetic acid and paraffin, and dried to obtain γ-aminopropyltriethoxysilane-modified nano-silica particles. Finally, calcined in a muffle furnace at 500°C for 3 hours to prepare nano-silica particles.
[0036] The ethanol aqueous solution (a mixture of anhydrous ethanol and water) is a mixture of anhydrous ethanol and deionized water in a volume ratio of 9:1.
[0037] After the γ-aminopropyltriethoxysilane modified nano-silica particles were quantitatively measured with acid orange, 15 mg of DDDEEKC-PEG1500-COOH- and 8 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride were mixed. At the same time, 20 mg of γ-aminopropyltriethoxysilane modified nano-silica was ultrasonically dispersed in the solution, and then 8 mg of hydroxysuccinimide was added. The above reactions were all carried out in a 4% ethanol / water solution. Stir at 4°C for 20 hours, centrifuge, and freeze-dry.
[0038] Disperse 25 mg of peptide-modified nano-silica in 2 ml of ethylene glycol aqueous solution, stir evenly, add 8% 1H,1H,2H,2H-perfluorooctyltriethoxysilane, stir at 4°C for 20 hours to obtain 1H,1H,2H,2H-perfluorooctyltriethoxysilane-modified nano-silica.
[0039] (3) Construction of superhydrophobic surface The final nano-silica was dissolved in ultrapure water at 7 mg / ml, dispersed evenly with a cell disruptor, and 200 ml was added to the well plate with the enamel slice, left to stand for 10 minutes, and the enamel slice was rinsed three times with ultrapure water and dried to obtain a super-hydrophobic enamel surface. The hydrophobic angle was reduced, but the hydrophobic angle was still greater than 150°, and the super-hydrophobic maintenance time did not change significantly.
[0040] Embodiment 4 (1) Preparation of Nano-Silica Add 3% deionized water to 220 ml of ethanol solution, then add 12 ml of tetraethyl orthosilicate TEOS, stir well to make it evenly dispersed, then add 12 ml of ammonia water, and let it react fully at 4°C for 8-12 hours to obtain 160 nm silica.
[0041] (2) Preparation of amphiphilic nano-silica Janus particles Add 1.5‱ mass fraction of nano-silica and deionized water into a beaker, ultrasonically disperse for 30 minutes, then add 15% mass fraction of paraffin and 5nmol~10nmol of surfactant-didecyldimethylammonium bromide, heat to 80°C, and stir at 11,000 rpm for 2 minutes to obtain silica nanoparticles with half of the sphere covered by paraffin.
[0042] The silica nanoparticles covered by paraffin were dispersed in an ethanol aqueous solution, ultrasonicated at 300W for 40 minutes, 8% of γ-aminopropyltriethoxysilane was added, transferred to a three-necked flask, pH 3 was adjusted with acetic acid, stirred at room temperature for 12 hours, and centrifuged at high speed to separate the nano-silica from the paraffin. The nano-silica particles were washed and centrifuged three times alternately with cyclohexane and anhydrous ethanol to remove acetic acid and paraffin, and dried to obtain γ-aminopropyltriethoxysilane-modified nano-silica particles. Finally, the nano-silica particles were prepared by calcining in a muffle furnace at 500°C for 3 hours.
[0043] The ethanol aqueous solution (a mixture of anhydrous ethanol and water) is a mixture of anhydrous ethanol and deionized water in a volume ratio of 9:1.
[0044] After the γ-aminopropyltriethoxysilane modified nano-silica particles were quantitatively measured with acid orange, 15 mg of DDDEEKC-PEG1000-COOH- and 12 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride were mixed. At the same time, 20 mg of γ-aminopropyltriethoxysilane modified nano-silica was ultrasonically dispersed in the solution, followed by the addition of 10 mg of hydroxysuccinimide. The above reactions were all carried out in a 4% ethanol / water solution. Stirred at 4°C for 20 hours, centrifuged, and freeze-dried.
[0045] Disperse 30 mg of peptide-modified nano-silica in 5 ml of ethylene glycol aqueous solution, stir evenly, add 12% 1H,1H,2H,2H-perfluorooctyltriethoxysilane, stir at 4°C for 20 hours to obtain 1H,1H,2H,2H-perfluorooctyltriethoxysilane-modified nano-silica.
[0046] (3) Construction of superhydrophobic surface The final nano-silica was dissolved in ultrapure water at 8 / ml, dispersed evenly with a cell disruptor, and 200ml was added to the well plate with the enamel slice, left to stand for 10 minutes, and the enamel slice was rinsed three times with ultrapure water and dried to obtain a super-hydrophobic enamel surface. The hydrophobic angle was reduced, but the hydrophobic angle was still greater than 150°. Embodiment 5 (1) Preparation of Nano-Silica Add 4% deionized water to 220 ml of ethanol solution, then add 14 ml of tetraethyl orthosilicate TEOS, stir well to make it evenly dispersed, then add 15 ml of ammonia water, and let it react fully at 4°C for 8-12 hours to obtain 220 nm silica.
[0047] (2) Preparation of amphiphilic nano-silica Janus particles Add 2‱ mass fraction of nano-silica and deionized water into a beaker, ultrasonically disperse for 30 minutes, then add 15% mass fraction of paraffin and 5nmol~10nmol of surfactant-didecyldimethylammonium bromide, heat to 85°C, and stir at 12000 rpm for 2 minutes to obtain silica nanoparticles with half of the sphere covered by paraffin.
[0048] The silica nanoparticles covered by paraffin were dispersed in an ethanol aqueous solution, ultrasonicated at 300W for 40 minutes, γ-aminopropyltriethoxysilane with a mass fraction of 15% was added, and the mixture was transferred to a three-necked flask, and the pH was adjusted to 3.5 with acetic acid, stirred at room temperature for 16 hours, and centrifuged at high speed to separate the nano-silica from the paraffin. The mixture was washed and centrifuged three times alternately with cyclohexane and anhydrous ethanol to remove acetic acid and paraffin, and dried to obtain nano-silica particles modified with γ-aminopropyltriethoxysilane. Finally, the nano-silica particles were prepared by calcining in a muffle furnace at 500° for 4 hours.
[0049] The ethanol aqueous solution (a mixture of anhydrous ethanol and water) is a mixture of anhydrous ethanol and deionized water in a volume ratio of 9:1.
[0050] After the γ-aminopropyltriethoxysilane modified nano-silica particles were quantitatively measured with acid orange, 20 mg of DDDEEKC-PEG500-COOH- and 15 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride were mixed. At the same time, 20 mg of γ-aminopropyltriethoxysilane modified nano-silica was ultrasonically dispersed in the solution, and then 12 mg of hydroxysuccinimide was added. The above reactions were all carried out in a 4% ethanol / water solution. Stir at 4°C for 20 hours, centrifuge, and freeze-dry.
[0051] Disperse 35 mg of peptide-modified nano-silica in 5 ml of ethylene glycol aqueous solution, stir evenly, add 4%-20% 1H,1H,2H,2H-perfluorooctyltriethoxysilane, stir at 4°C for 20 hours to obtain 1H,1H,2H,2H-perfluorooctyltriethoxysilane-modified nano-silica.
[0052] (3) Construction of superhydrophobic surface The final nano-silica was dissolved in ultrapure water at 9 mg / ml, dispersed evenly with a cell disruptor, and 200 ml was added to the well plate with the enamel slice, left to stand for 10 minutes, and the enamel slice was rinsed three times with ultrapure water and dried to obtain a super-hydrophobic enamel surface. The hydrophobic angle was reduced, but the hydrophobic angle was still greater than 150°, and the super-hydrophobic maintenance time did not change significantly.
[0053] Embodiment 6 (1) Preparation of Nano-Silica Add 1% deionized water to 220 ml of ethanol solution, then add 5 ml of tetraethyl orthosilicate TEOS, stir well to make it evenly dispersed, then add 4 ml of ammonia water, and let it react fully at 4°C for 8-12 hours to obtain 50 nm silica.
[0054] (2) Preparation of amphiphilic nano-silica Janus particles Add 1‱ mass fraction of nano-silica and deionized water into a beaker, ultrasonically disperse for 30 minutes, then add 10% mass fraction of paraffin and 5nmol~10nmol of surfactant-didecyldimethylammonium bromide, heat to 70 degrees, and stir at 9000 rpm for 2 minutes to obtain silica nanoparticles with half of the sphere covered by paraffin.
[0055] The silica nanoparticles covered by paraffin were dispersed in an ethanol aqueous solution, ultrasonicated at 300W for 30 minutes, 4% of γ-aminopropyltriethoxysilane was added, transferred to a three-necked flask, pH 3 was adjusted with acetic acid, stirred at room temperature for 12 hours, and centrifuged at high speed to separate the nano-silica from the paraffin. The nano-silica was washed and centrifuged three times alternately with cyclohexane and anhydrous ethanol to remove acetic acid and paraffin, and dried to obtain γ-aminopropyltriethoxysilane-modified nano-silica particles. Finally, the nano-silica particles were prepared by calcining in a muffle furnace at 500° for 3 hours.
[0056] The ethanol aqueous solution (a mixture of anhydrous ethanol and water) is a mixture of anhydrous ethanol and deionized water in a volume ratio of 9:1.
[0057] After the γ-aminopropyltriethoxysilane modified nano-silica particles were quantified with acid orange for the number of amino groups, 10 mg of DDDEEKC-PEG100-COOH- and 5 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride were mixed. At the same time, 20 mg of γ-aminopropyltriethoxysilane modified nano-silica was ultrasonically dispersed in the solution, and then 5% of hydroxysuccinimide was added. The above reactions were all carried out in a 4% ethanol / water solution. Stir at 4°C for 20 hours, centrifuge, and freeze-dry.
[0058] Disperse 20 mg of peptide-modified nano-silica in 5 ml of ethylene glycol aqueous solution, stir evenly, add 4% 1H,1H,2H,2H-perfluorooctyltriethoxysilane, stir at 4°C for 20 hours to obtain 1H,1H,2H,2H-perfluorooctyltriethoxysilane-modified nano-silica.
[0059] (3) Construction of superhydrophobic surface The final nano-silica was dissolved in ultrapure water at 6 mg / ml, dispersed evenly with a cell disruptor, and 200 ml was added to the well plate with the enamel slice, left to stand for 10 minutes, and the enamel slice was rinsed three times with ultrapure water and dried to obtain a super-hydrophobic enamel surface. The hydrophobic angle did not change significantly, the hydrophobic angle was 170 degrees, and the super-hydrophobic maintenance time did not change significantly.
[0060] See also Figures 1 to 6 : Figure 1 (a) Contact angle of water droplet on enamel surface at 0 min, Figure 1 (b) Contact angle of water droplet on enamel surface for 30 minutes. Figure 1 (c) is the contact angle of the enamel surface after co-culture with artificial saliva for three days; Figure 2 , further illustrating the hydrophobic properties of the coating surface; Figure 3-Figure 5 In the figure, a represents nano-silica, b represents nano-silica modified with γ-aminopropyltriethoxysilane, c represents nano-silica modified with polypeptide, and d represents nano-silica modified with 1H,1H,2H,2H-perfluorooctyltriethoxysilane; Figure 3 , the particle size of the synthesized particles changes, and their particle sizes increase in sequence; Figure 4 , EDS image, during the synthesis of amphoteric particles, fluoride ions appeared in the nano-silica modified with 1H,1H,2H,2H-perfluorooctyltriethoxysilane; Figure 5 , EDS diagram, the nitrogen content changes significantly during the synthesis of amphoteric particles.
[0061] Figure 6 , FT-IR graph of the hydrophobic coating on the enamel surface, 1096cm-1 and 800cm-1 are the characteristic absorption peaks of nano-silica, 1311cm-1 is the characteristic absorption peak of fluoride ion, 1540cm-1 is the characteristic absorption peak of carbonyl, and 3620cm-1 is the characteristic absorption peak of hydroxyl; Figure 7 (a) Electron micrograph of enamel. Figure 7 (b) is an electron micrograph of the coating, showing nano-silica attached to the enamel surface.
[0062] In summary, the amphiphilic Janus particles were constructed using the adhesion polypeptide sequence of the acquired membrane as the bonding end and 1H,1H,2H,2H-perfluorooctyltriethoxysilane as the hydrophobic end, and the morphology of the particles was regular and the structure was controllable.
[0063] The amphiphilicity of SiO2Janus particles is used to orient them on the surface, with the hydrophilic hemisphere facing the surface and the hydrophobic hemisphere facing the air side, thus achieving super-hydrophobicity on the surface. At the same time, the specific amino acid sequence on the polypeptide sequence specifically adsorbs with the hydroxyapatite on the surface, fixing the SiO2Janus particles on the surface, so that the coating is formed efficiently and quickly.
[0064] The contact angle between the super-hydrophobic coating prepared by the present invention and water is as high as 160°, and the contact angle of water dropped onto the coating surface 30 minutes later is still greater than 150°. When the coating is co-cultured with artificial saliva for 3 days, the surface still has a super-hydrophobic effect.
[0065] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for constructing a super-hydrophobic surface based on amphiphilic hollow silica Janus nanoparticles, characterized in that: The method comprises the following preparation steps: Step 1: preparing monodisperse spherical silica particles through a hydrolysis-condensation reaction; Step 2: Add nano-silica to deionized water, add solid paraffin and surfactant after ultrasonication, heat to 70-90°C and emulsify at high speed for 2 minutes to obtain Pickering emulsion, cool and wash to obtain silica nanoparticles half-covered by paraffin; Step 3, dispersing the silica nanoparticles prepared in step 2 in an ethanol aqueous solution, stirring evenly, adding γ-aminopropyltriethoxysilane, then adjusting the pH, and then stirring at room temperature for 12 hours to obtain γ-aminopropyltriethoxysilane-modified silica nanoparticles; Step 4: After the number of amino groups of the nano-silica obtained in step 3 is quantified by acid orange II, DDDEEKC-PEG100-2000-COOH - After mixing with 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride for 30 minutes, the mixture was added to the ultrasonically dispersed γ-aminopropyltriethoxysilane-modified nano-silica solution, followed by the addition of hydroxysuccinimide. The above reactions were all carried out in a 4% ethanol / water solution. The solution was then stirred at 4°C for 20 hours, centrifuged and freeze-dried to obtain polypeptide-modified nano-silica. Step 5, adding the nano-silica obtained in step 4 to an ethylene glycol aqueous solution, adding 1H,1H,2H,2H-perfluorooctyltriethoxysilane, and stirring for 20 hours to obtain nano-silica particles modified with 1H,1H,2H,2H-perfluorooctyltriethoxysilane; Step 6: Dissolve the nano-silica obtained in step 5 in ultrapure water at 6-10 mg / ml, disperse it evenly with a cell disruptor, take 200 ml and add it to the well plate with the enamel slice, let it stand for 10 minutes, rinse the enamel slice three times with ultrapure water, and dry it to obtain a superhydrophobic enamel surface.
2. A method for constructing a super-hydrophobic surface based on amphiphilic hollow silica Janus nanoparticles according to claim 1, characterized in that: In step 1, the particle size of the medium-nano silica is 20-500 nm.
3. A method for constructing a super-hydrophobic surface based on amphiphilic hollow silica Janus nanoparticles according to claim 1, characterized in that: In step 2, the mass fraction of water is 80%-90%, the mass fraction of nano-silicon dioxide is 1‱-2‱, the mass fraction of paraffin is 10%-20%, and the surfactant is 5nmol~10nmol.
4. A method for constructing a super-hydrophobic surface based on amphiphilic hollow silica Janus nanoparticles according to claim 1, characterized in that: In step 2, the emulsification speed is 5000-18000 rpm.
5. A method for constructing a super-hydrophobic surface based on amphiphilic hollow silica Janus nanoparticles according to claim 1, characterized in that: In step 2, the emulsification temperature is 70-90°C.
6. A method for constructing a super-hydrophobic surface based on amphiphilic hollow silica Janus nanoparticles according to claim 1, characterized in that: In step three, the ethanol aqueous solution is a mixed solution of anhydrous ethanol and water, the volume ratio is 90-50ml:10-50ml, the mass fraction of γ-aminopropyltriethoxysilane is 4%-20%, and the pH is adjusted to 3-4.
7. The method for constructing a super-hydrophobic surface based on amphiphilic hollow silica Janus nanoparticles according to claim 1, characterized in that: In step 4, NH4 + With COOH - The molar ratio of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride to COOH is 3-5:
1. - The molar ratio of ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride to N-hydroxysuccinimide is 6-10:1, the molar ratio of ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride to N-hydroxysuccinimide is 1:1, and the molecular weight distribution range of polyethylene glycol is PEG100-2000.
8. The method for constructing a super-hydrophobic surface based on amphiphilic hollow silica Janus nanoparticles according to claim 1, characterized in that: In step five, the volume ratio of ethylene glycol to water in the ethylene glycol aqueous solution is 3-7:7-3, and the mass fraction of 1H,1H,2H,2H-perfluorooctyltriethoxysilane is 4%-20%.
Citation Information
Cited By
Dual-actuated dentin mineralization desensitizing material with hydrodynamic configuration and preparation method thereof
CN122681714A